2020
DOI: 10.3390/jcm9030684
|View full text |Cite
|
Sign up to set email alerts
|

Pain Detection with Bioimpedance Methodology from 3-Dimensional Exploration of Nociception in a Postoperative Observational Trial

Abstract: Although the measurement of dielectric properties of the skin is a long-known tool for assessing the changes caused by nociception, the frequency modulated response has not been considered yet. However, for a rigorous characterization of the biological tissue during noxious stimulation, the bioimpedance needs to be analyzed over time as well as over frequency. The 3-dimensional analysis of nociception, including bioimpedance, time, and frequency changes, is provided by ANSPEC-PRO device. The objective of this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…Beside tests within controlled laboratory environments, the second generation device was clinically validated by means of a comparison with a reference commercial device, both methodologies based on electrodermal activity identification. The observational study in awake postoperative patients concluded that Anspec-PRO performs equally well as the commercial device under similar conditions, representing proof of concept for the prototype device [20]. Moreover, Anspec-PRO is currently under tests in a clinical trial on anesthetized patients for its validation in surgery context, in comparison to other two commercial pain monitors.…”
Section: Introductionmentioning
confidence: 78%
See 2 more Smart Citations
“…Beside tests within controlled laboratory environments, the second generation device was clinically validated by means of a comparison with a reference commercial device, both methodologies based on electrodermal activity identification. The observational study in awake postoperative patients concluded that Anspec-PRO performs equally well as the commercial device under similar conditions, representing proof of concept for the prototype device [20]. Moreover, Anspec-PRO is currently under tests in a clinical trial on anesthetized patients for its validation in surgery context, in comparison to other two commercial pain monitors.…”
Section: Introductionmentioning
confidence: 78%
“…The already available results indicate that the developed prototype is able to capture the signaling pathways and deliver an objective measure for pain. A clinical trial was conducted in patients recovering from anesthesia, and the results show a good performance for the prototype to identify changes in pain pathways by measuring the skin impedance [20]. As the aim of this paper is to illustrate the development methodology of our prototype, the existing prior results with more details about the previous work can be found in Section 3.7.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A PD model for analgesia as a separate output variable to be controlled is currently missing. Presently, enabled by recent commercial devices availability for objective pain level assessment, ongoing efforts in clinical trial testing [72], [73] are expected to provide the necessary data for estimating the PD model. The hemodynamic system is described as a first order plus dead time approximation of the PKPD effects.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, there is no pharmacodynamic model for Remifentanil. In this regard, the authors developed a methodology for detecting nociceptor simulation which has been successfully validated in healthy volunteers [50] but also in post-operative ICU patients [73]. Ongoing clinical studies in unconscious patients at Ghent University Hospital will provide updates for future versions of the simulator.…”
Section: Limitationsmentioning
confidence: 99%